An observational study on immunohistochemical expression profile of PCNA in urothelial carcinoma of bladder and association with clinicopathological parameters - Raman, Srinivasan; Sudalaimuthu, Muthu; Amitkumar, Kalaivani; John, Jaison Jacob (Journal of Neonatal Surgery, 2025)
Background: Bladder cancer remains as one of the most common cancers of the urinary tract, with higher rates of incidence and heterogenous molecular and histological components affecting its prognosis. Proliferating Cell Nuclear Antigen (PCNA) is a protein and immunohistochemical (IHC) biomarker associated with the G1/S phase of the cell cycle that is essential for the proliferation of neoplastic cells. This study aimed to describe the histomorphological aspects of UC of the bladder. To evaluate the expression of PCNA with clinicopathological parameters of the disease such as age, gender, clinical features, site, configuration, histological grade, stage, and lymphovascular invasion (LVI). Materials and methods: Forty histologically confirmed cases of urothelial carcinoma (UC) from the Department of Pathology at a tertiary care centre in South India were analyzed. PCNA immunohistochemistry was performed, assessing staining intensity and percentage of positive tumor cells. Chi-square tests evaluated associations with clinicopathological features such as age, gender, clinical presentation, tumor site, configuration, grade, type, stage, and LVI. Results: The expression of the PCNA was found to be significantly associated with sessile tumors (p=0.023), higher histological grading (p=0.001), advanced stage tumors (p < 0.001) and LVI (p = 0.036), suggesting possible association as a marker of tumor aggressiveness and progression. No associations were found with the parameters such as patient age, gender, clinical presentation, or location of the tumor concerning PCNA expression. Conclusions: Our study demonstrated PCNA overexpression in sessile, high-grade tumors, muscle-invasive tumors, LVI and with advanced tumor stage. This shows that PCNA may serve as a marker of proliferation and aggressiveness aiding in prognosis, treatment planning and decision making. More studies are required for validation of our findings